Governança global da inteligência artificial no combate à desinformação: o impacto do Ato de IA da União Europeia. - Olivieri, Gabriel Augusto de Paula [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
Recently, there has been great progress in the field of Artificial Intelligence (AI), leading to widespread access by the population to tools that use this technology. However, with the democratization of AI comes possible risks, such as its use to generate disinformation. In this paper, we seek to answer the following question: what is the role of global governance in seeking to mitigate the risks of the use of AI for disinformation? We will analyze the AI Act (AIA), recently adopted by the European Union (EU). We believe that the bloc has made the most significant advances in AI regulation in recent years. To this end, we will first discuss the topic of AI itself, trying to explain what it is and its impact on society, starting with a reflection on the possible uses of AI tools to generate disinformation. Then, thinking about the question of global governance, we will analyze the main initiatives and projects related to the regulation of AI, seeking to understand the actions being taken to mitigate the risks of the use of AI for disinformation. Finally, we will examine the AI Act and the impacts that this legislation may have on International Relations (IR).

Recentemente, houve grande avanço no campo da Inteligência Artificial (IA), levando a um amplo acesso da população a ferramentas que utilizam essa tecnologia. No entanto, com a democratização da IA, decorrem possíveis riscos, como sua utilização para gerar desinformação. Neste trabalho, buscamos responder à seguinte pergunta: qual é o papel da governança global na busca por mitigar os riscos do uso da IA para desinformação? Analisaremos o Ato de IA (AIA), recém adotado no âmbito da União Europeia (UE). Entendemos que o bloco foi a instituição que realizou os avanços mais significativos no âmbito da regulamentação de IA nos últimos anos. Para tanto, inicialmente discutiremos o tema da IA propriamente dito, buscando explicar o que ela é e seu impacto na sociedade, a partir de uma reflexão sobre os possíveis usos de ferramentas de IA para gerar desinformação. Em seguida, pensando na questão da governança global, analisaremos as principais iniciativas e projetos relacionados à regulamentação da IA, buscando compreender as ações que estão sendo tomadas para mitigar os riscos do uso da IA para desinformação. Por fim, será examinado o Ato de IA e os impactos que essa legislação pode ter nas Relações Internacionais (RI).
Global governance of artificial intelligence in the fight against disinformation: the impact of the European Union's AI Act.
Keywords: Relações internacionais; Governança; Inteligência artificial; Desinformação; União Europeia; International relations; Governance; Artificial intelligence; Disinformation; European Union